BUILDING A CONSTITUTIONAL AWARE CULTURE TO CREATE A DEMOCRATIC LAW STATE - Jimly Asshiddiqie (LKKI Fakultas Syariah dan Hukum Universitas Islam Negeri Ar-Raniry, 2023)
This article investigates on how the 1945 Constitution has changed the landscape of Indonesian’s legal system as well as creating democratic law state. In contrast, before the amendment of 1945 Constitution, the state power has centred in the hand of president, including the power of legislative, judicative, and also executive. In this period of time, it is hard to build constitutional awareness as people do not feel a democratic law state, affecting the people have low trust to the government. This condition has asked for amending the constitution and sharing state power instead of centring in one hand with principle of check and balances. This article has used constitutional black-letter law method, focusing on constitution norms in specific articles as main data. The main points can conclude that the 1945 Constitution after amendment has democratically created law state as several foundamental rights of people has been absorbed in the Constitution 1945, including human rights and priciple check and balances. Abstrak: Artikel ini membahas tentang bagaimana Undang-Undang Dasar 1945 telah mengubah wajah sistem hukum Indonesia serta menciptakan negara hukum demokratis. Hal ini bertolak belakang sebelum adanya amandemen Undang-Undang Dasar 1945, dimana kekuasaan negara berpusat di tangan presiden, bersamaan dengan kekuasaan legislatif, yudikatif, dan eksekutif. Pada periode tersebut sangat susah membangun kesadaran berkonstitusi karena rakyat tidak merasakan bernegara secara demokratis, yang mengakibatkan rendahnya kepercayaan masyarakat kepada pemerintah. Kondisi seperti ini mengakibatkan tuntutan untuk mengamandemen undang-undang dasar dan membagi kekuasan negara dengan prinsip saling memeriksa dan berimang, bukan mempusatkan pada satu tangan kekuasaan. Artikel ini menggunakan metode constitutional black-letter law denga fokus pada norma konstitusi yang terdapat pada pasal-pasal khusus sebagai data utama. Kesimpulan utama dalam artikel ini adalah Undang-Undang Dasar 1945 setelah diamandemen telah menciptakan negara demokratis. Beberapa hak-hak dasar rakyat telah di serap didalamnya, termasuk hak asasi manusia dan prinsip-prinsip saling periksa dan berimbang. Kata Kunci: Kesadaran Berkonstitusi, Negara Hukum Demokratis, Undang-Undang Dasar 1945